058. A Rare Case: Anterior Wall Rectum Perforation Due to Intrauterine Device Migration - Bhaktiyasa, I Nyoman Marsel Rama Grandita; Mahayasa, I Made (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical Education, 2024)
Background : Intrauterine devices (IUDs) are widely used for contraception due to their long-acting, safe, and effective nature in preventing pregnancy. However, common side effects and complications, such as vaginal bleeding, expulsion, displacement, translocation, and perforation necessitate attention, with translocation and perforation being rare but potentially severe, warranting prompt removal according to WHO recommendations. This study aims to document and analyze a rare case of rectal perforation resulting from the migration of an IUD. Case : A report was made from 31-year-old pregnant woman with a history of two cesarean sections presented with 10-day abdominal pain and an IUD inserted 42 days post-surgery, which MRI revealed had translocated into the left anterolateral rectal wall, prompting retroscopy for extraction. Uterine perforation and IUD migration into adjacent organs can result in various complications, including uterine, bladder, and intestinal perforation, with initial symptoms potentially being asymptomatic, emphasizing the need for routine check-ups. Retrieval of migrated IUDs can be achieved through methods such as endoscopy, laparoscopy, or laparotomy, as illustrated in a case involving a patient with abdominal pain and imaging evidence of IUD translocation to the rectum's anterior wall, managed through less invasive rectoscopy. Conclusion: Translocated IUDs may exhibit varying symptoms or none at all, necessitating removal regardless of type or location, with management guided by radiological and endoscopic findings alongside understanding abdominal organ anatomy